การเปรียบเทียบผลสัมฤทธิ์ทางการเรียนและการคิดแก้ปัญหา โดยใช้กิจกรรม การเรียนรู้แบบโครงงานกับการจัดกิจกรรมการเรียนรู้แบบกลุ่มร่วมมือ - ภูปลื้ม, สมลักษณ์ (Journal of Graduate School Sakon Nakhon Rajabhat University, 2018)
The objectives of this research were to 1) develop learning activity management plans of the 5th learning unit of Economics subject on the topic Sufficiency Economy Philosophy for Mathayomsuksa 1 students using project-based approach and student teams achievement divisions (STAD) approach to reach the effectiveness criterion at 80/80, 2) figure out the effectiveness index of these learning activity management plans, 3) compare the learning achievement of Mathayomsuksa 1 students between learning with project-based approach and STAD approach; 4) compare the problem solving thinking of Mathayomsuksa 1 students between learning with project-based approach and STAD approach, and 5) study the satisfaction of Mathayomsuksa 1 students after learning through project-based approach and STAD approach. Sampling group of this research, selected by cluster sampling method, consisted of 100 Mathayomsuksa 1 students from 2 classrooms (50 students from M.1/10 and 50 students from M.1/11) at Anukoolnaree School in Muang district, Kalasin province under the Office of Secondary Educational Service Area 24, during the second semester of academic year 2014. Research instruments included; 15 learning activity management plans based on project-based approach (for M.1/10), 15 learning activity management plans based on STAD approach (for M.1/11), learning achievement test on the topic Sufficiency Economy Philosophy which consisted of 30 objective questions-4 possible answers (with index of consistency between 0.60-1.00, discrimination (B) from 0.23 to 0.63, and reliability (r) at 0.86), measurement test for problem solving thinking on the topic Sufficiency Economy Philosophy which consisted of 2 items (with index of consistency between 0.60-1.00, discrimination (B) from 0.41 to 0.75, and reliability (r) at 0.72). Data analysis was made through mean, percentage, standard deviation, and t- test (dependent samples). The findings were as follows : 1. The effectiveness of developing learning activity management plans on the topic Sufficiency Economy Philosophy under the 5th learning unit of Economics subject for Mathayomsuksa 1 students using project-based approach indicated 85.53/82.87 while the 83.69/81.40 was found with STAD approach. 2. The effectiveness index of learning activity management plans of project-based approach and STAD approach was 0.5214 and 0.5088 respectively. These could refer to the increase of study progress of students at 52.14% and 50.88%. 3. Learning achievements of students after learning through project-based approach and STAD approach were not different. 4. Scores of students’ problem solving thinking between learning through project-based approach and STAD approach were different with statistical significance at .05 level. 5. Overview of students’ satisfaction towards learning through project-based approach and STAD approach indicated the highest level of satisfaction.